2001
DOI: 10.1182/blood.v97.11.3354
|View full text |Cite
|
Sign up to set email alerts
|

Plasma elevation of stromal cell–derived factor-1 induces mobilization of mature and immature hematopoietic progenitor and stem cells

Abstract: The chemokine, stromal cell-derived factor-1 (SDF1), is produced in the bone marrow and has been shown to modulate the homing of stem cells to this site by mediating chemokinesis and chemotaxis. Therefore, it was hypothesized that elevation of SDF1 level in the peripheral circulation would result in mobilization of primitive hematopoietic stem and progenitor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
323
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 483 publications
(345 citation statements)
references
References 31 publications
18
323
0
3
Order By: Relevance
“…These increases were not specific to this myeloproliferative disorder as high levels of SDF-1 were also observed in the plasma of patients with PV ( Figure 6). The elevation of SDF-1 observed in the blood of the animal model and of the PMF patients were modest (~2-4-fold) (Figure 2 and 6) when compared to the levels required to experimentally induce stem/progenitor cell mobilization in NOD/SCID mice (25-fold) 34,35 and are, therefore, unlikely to be responsible for a gradient driven mobilization of stem/progenitor cells.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These increases were not specific to this myeloproliferative disorder as high levels of SDF-1 were also observed in the plasma of patients with PV ( Figure 6). The elevation of SDF-1 observed in the blood of the animal model and of the PMF patients were modest (~2-4-fold) (Figure 2 and 6) when compared to the levels required to experimentally induce stem/progenitor cell mobilization in NOD/SCID mice (25-fold) 34,35 and are, therefore, unlikely to be responsible for a gradient driven mobilization of stem/progenitor cells.…”
Section: Discussionmentioning
confidence: 90%
“…The concentration of soluble SDF-1 in the blood, however, increases in association with many of the conditions that induce stem/progenitor cell mobilization. Both sustained elevations of SDF-1 in NOD/SCID mice delivered by an adenoviral vector delivery system [34][35][36] , and chronic administration to the animals of SDF-1 peptide analogs 37,38 , result in mobilization of stem/ progenitor cells. In addition, increased plasma SDF-1 levels are also observed during mobilization induced by sulfated glycans 39 .…”
Section: Introductionmentioning
confidence: 99%
“…12 On the other hand, it has been demonstrated that the higher concentration of CXCL12 in the peripheral circulation facilitates the mobilization of CD34 cells in mice. Hattori et al 18 have reported that the overexpression of CXCL12 in the peripheral circulation (for example, the i.v. injection of an recombinant adenovirus expressing CXCL12) results in the mobilization of haematopoietic cells with repopulating capacity, progenitor cells and precursor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Direct evidence for the role of SDF-1 in regulating mobilization of pro-angiogenic BM cells in vivo has been demonstrated by plasma elevation of SDF-1, which stimulates mobilization of CXCR4 + BM cells, including HSCs and EPCs [31,32]. Increased elevation of SDF-1 concentration in the blood has been observed in ischemic models, while its concentration in the BM was decreased, thereby resulting in the mobilization of the pro-angiogenic cells [14,18,33].…”
Section: Sdf-1 Is the Primary Chemokine That Supports Mobilization Ofmentioning
confidence: 99%